Penetapan Kadar Total Fenol dan Aktivitas Antioksidan dari Jus Buah Lima Spesies Jeruk (Citrus sp.) - Dadang Juanda (JURNAL FARMASI GALENIKA, 2015)
Jeruk or Citrus is a fruit that is often consumed by Indonesia people, there are several kind of citrus such as C. sinensis, C. hystrix, C. aurantifolia, C.maxima and C. nobilis. The active compounds known from these plants are phenolic compounds which have antioxidant activity. The research was carried out to determine the total phenol content and antioxidant activity of some of the citrus. Squeezed citrus fruit were freeze dried to obtain dry juice. The levels of total phenols from juice were determined using Folin Ciocalteau reagent while antioxidant activity was tested in vitro using the method of reduction of free radical 1,1-diphenyl-2-picryl Hydrazyl (DPPH). Total phenol content of C. sinensis, C. hystrix, C. aurantifolia, C. maxima and C. nobilis respectively were 98,6; 141,7; 81,7; 71,3; 67,4 (mg gallic acid/100 g juice). EC50 (efficient concentration)of C. sinensis, C. hystrix, C. aurantifolia, C. maxima and C. nobilis respectively were 732.00; 1255.07; 1631.80; 1739.72; 2192.2 Âµg/mL. Keywords: Kata kunci : Citrus sp , Jeruk, kadar fenolat total, antioksidan, DPPH